Pengaruh Reputasi Penjamin Emisi, Pengungkapan Modal Intelektual dan Persentase Penawaran Saham pada Underpricing Saham IPO - Arief Alvierri Doda; I Gusti Ketut Agung Ulupui; Gentiga Muhammad Zairin (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
The purpose of this study is to analyze the effect of Underwriter Reputation, Intellectual Capital Disclosure and Percentage of Stock Offerings on IPO Stock Underpricing. Stock price reports at the time of IPO on the IDN Financials website and prospectus reports on the E-IPO website are used as secondary data in this study. The sample was selected using purposive sampling method and obtained a total sample of 64 data from 64 companies that met the criteria. The reputation of the underwriter has no effect on underpricing because the reputation of the underwriter is not part of the internal company so that investors think it will not affect the company's performance. The intellectual capital disclosure variable can reduce uncertainty for investors because it can provide information about the Company so that it has a negative effect on underpricing. The variable percentage of share offerings has no effect because the number of shares does not provide information regarding the growth prospects and potential of the Company as a whole.